Making Sense of Fairness in Sports - Murray, Thomas H. (The Hastings Center report, 2010)
Cheating evolves constantly. Dozens of athletes were barred from the Winter Olympics for taking banned substances. Gene doping is on the horizon. Questions have arisen about which athletes count as “female.” What does it take to keep sports fair? And what does fairness require?